Development of Sparkol VideoScribe-Based Physics Learning Videos on Elasticity Material - Roidatuljanah, Umiyati; Bahtiar, Bahtiar; Ilham, Ilham (Universitas PGRI Semarang, 2023)
The emergence of the Covid-19 outbreak which has shocked the world today has caused the Indonesian government to issue a distance learning policy. This policy demands the creativity of teachers to be able to develop various learning media in order to continue to carry out a good educational process during a pandemic. This study aims to develop physics learning videos that are valid, practical, and easily understood by students. This type of research is Research and Development (RD) using the ADDIE development model. Videos are developed on elastic material using the Sparkol VideoScribe application. The research instrument was a validation questionnaire for material experts, media experts, and physics teachers, and the responses of class XI students at SMAN 1 Brang Rea. The learning videos developed are very feasible based on the validation results of material experts at 84%, media experts at 83%, and physics teachers at 94%, with an average percentage of 84%. The results of the student response test to the video obtained a percentage of 90% so it was categorized as very good. Thus the video learning physics based on Sparkol VideoScribe on elasticity material is very appropriate to be used as a medium in learning physics.